“Without a man’s decision, nothing works”: Building resilience to Rift Valley fever in pastoralist communities in Isiolo Kenya - Mutambo, Irene N.; Bett, Bernard K.; Bukachi, S.A. (2025)
Rift Valley fever (RVF) is a zoonotic disease that affects both livestock and humans. Men and women in pastoralist communities are vulnerable to RVF risk exposure because of their different roles and reliance on livestock products. This study sought to understand how ownership and decision-making in pastoralist male and female-headed households influence coping mechanisms and resilience to Rift Valley fever (RVF), using the three resilience capacities of absorptive, adaptive, and transformative. This study was conducted in two sub-counties (Garbatulla) and Merti), Isiolo County, Kenya. Data were collected through 16 focus group discussions and 13 key informant interviews with pastoralists and animal and human health stakeholders. The findings indicate that traditionally, men have the final say on decisions related to livestock ownership and make overall household decisions. Pastoralist men and women employ different approaches, including hygiene practices and mosquito nets, community knowledge dissemination, establishment of new businesses, utilization of healthcare, and indigenous medicines, to reduce the effects of RVF in both humans and livestock. They also collaborated with community disease surveillance initiatives to strengthen disease surveillance networks and gain access to county government support. This process fosters resilience, community empowerment, and transformative and sustainable adaptation responses to RVF.